1963
DOI: 10.1161/01.res.13.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin II on the Intact Forearm Veins of Man

Abstract: Angiotensin II was injected into an isolated venous segment in eighteen human subjects and administered intravenously into a systemic vein in five other subjects. Injections of angiotensin II into an intact isolated venous segment produced no constriction of the segment. Intravenous systemic infusion of angiotensin II produced a slight constriction of the isolated venous segment in three subjects (mean 44 mm H 2 O) and no constriction of the segment in two subjects. The constriction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1964
1964
1992
1992

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…It is conceivable that release of renin from the kidney by furosemide with subsequent angiotensin II production could have caused generation of a vasodilator substance in the vasculature to produce the effects we observed. In contrast to its profound effects on arterioles, angiotensin II produces little or no direct constriction of capacitance vessels (DePasquale and Burch, 1963;Somlyo and Sorrilyo, 1966). It has been observed in several vascular beds that angiotensin II stimulates production of a vasodilator prostaglandin that modulates the arteriolar constriction produced by angiotensin (Messina et al, 1976;Gryglewski et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that release of renin from the kidney by furosemide with subsequent angiotensin II production could have caused generation of a vasodilator substance in the vasculature to produce the effects we observed. In contrast to its profound effects on arterioles, angiotensin II produces little or no direct constriction of capacitance vessels (DePasquale and Burch, 1963;Somlyo and Sorrilyo, 1966). It has been observed in several vascular beds that angiotensin II stimulates production of a vasodilator prostaglandin that modulates the arteriolar constriction produced by angiotensin (Messina et al, 1976;Gryglewski et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature change suggests the mechanism is venous constriction as described for levarterenol. However, injection of angiotensin into an intact isolated segment of a large superficial vein in the human forearm produces little evidence of venous constriction (56), and local administration has little effect on the veins of animals (2,8,55,57). On the other hand, intravenous administration produces a slight rise in the pressure within the intact presumably isolated segment of superficial forearm vein (56) and a decrease in forearm venous compliance (58).…”
Section: Discussionmentioning
confidence: 99%
“…Thus; the volume and/ or renin state prior to the administration of the inhibitor may determine the venous response and may explain the contrasting claims by previous investigators as some have reported that angiotensin II has a marked venoconstrictive effect (DePasqualle and Burch, 1963) but this was not confirmed by others (Tsuru et al, 1976). These discrepant results may also reflect differences due to varying bradykinin levels, since it is known that the converting enzyme inhibitor may potentiate the action of bradykinin (see below), which relaxes venous smooth muscle (Levy, 1972).…”
Section: Hemodynamic Effects Of Converting Enzyme Inhibitor In Normalmentioning
confidence: 98%